The long riders [videorecording (DVD)] - Hill, Walter, 1942-; Carradine, David; Carradine, Keith, 1949-; Carradine, Robert, 1954-; Keach, James; Keach, Stacy; Quaid, Dennis; Quaid, Randy, 1950-; Guest, Christopher; Guest, Nicholas, 1955- (Western legends., 2001)
Four theatrical families of the 1980's recreate the most wanted criminal families of the 1860's. This portrayal of the Jesse James gang is a rapidfire succession of thrilling moments -- the bandits' lightning attacks on banks, trains and stagecoaches ; their hairbreadth escapes from the law ; Jesse's jubilant wedding celebration ; and the tragic Great Northfield, Minnesota raid.